Comparison of Maternal Health Service Satisfaction Level of National Health Coverage and Non National Health Coverage Patients in Bandung Mother and Child Hospital - Rika Yuntiani; Eppy Darmadi Achmad; Henni Djuhaeni (Althea Medical Journal, 2016)
Background: Healthcare is financially inaccessible to some people. This results in deterioration of patients’ condition or even death, which is proven by the high level of Maternal Death Rate in Indonesia. The government implemented the National Health Coverage (NHC) system to ensure the provision of quality health care for the entire community. This study aimed to examine the NHC and non-NHC patients’ perception to quality maternal healthcare services.Methods: This study was an analytic cross-sectional study conducted from August–October 2014. One hundred and twenty six respondents from Kota Bandung Mother and Child Hospital were included. The tool used in this study was a validity and reliability-tested questionnaire encompassing five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. The Kolmogorov-Smirnov test was used to test the hypothesis.Results: The study showed that the majority of NHC(75%) and non-NHC patients (89%) ware unsatisfied with the maternal healthcare services. Most patients felt unsatisfied towards the reliability dimension which involved complicated referral procedures and examination time that failed to comply with what was promised.Conclusions: There is no difference between NHC and non-NHC patients’ level of satisfaction of maternal health care service in Bandung Mother and Child Hospital. [AMJ.2016;3(3):425–29]DOI: 10.15850/amj.v3n3.869